Peroxidases and differentiation in Cucurbits - Loy, James Brent, author; Denna, Donald W., advisor; Foskett, Richard L., committee member; Wood, Donald R., committee member; Johnson, Gestur, committee member; Ross, Cleon, committee member (Colorado State University. Libraries, 1967)
An investigation of the isoperoxidases in the family Cucurbitaceae and their relationship to genetic dwarfing was conducted. Histochemical, quantitative, and electrophoretic techniques were integrated in the study. An examination of stem sections of squash and muskmelon revealed that peroxidase was strongly localized in the epidermis, the sclerenchymatous ring, and the xylem. No qualitative peroxidase differences were observed between the stem sections of bush and vine lines of squash and muskmelon. A gross analysis of the amount and distribution of lignin in the stem sections also revealed no apparent differences between the lignified areas and the regions of high peroxidase activity in the stem sections. The exception was the high peroxidase activity found in the non-lignified epidermal tissue. The results do not support peroxidase involvement in dwarfing mechanisms in the plants studied, There were varietal differences in the levels of total peroxidase activity among the ten squash lines studied. However, no inverse relationship between peroxidase activity and the degree of stem elongation was found. There were no significant differences in peroxidase activity between the isogenic bush and vine lines of squash. The anodic isoperoxidase patterns of the squash lines were found to vary considerably, while the cathodic isoperoxidases among the squash line were fairly uniform and much easier to discern than the anodic isoperoxidases. There were no apparent consistent differences in the isoperoxidase patterns between the bush and vine lines. The isoperoxidase patterns of the isogenic bush and vine lines of squash were nearly identical. Thus, no relationships between the isoperoxidase patterns and the bush habit of growth were evident. Both the anodic and the cathodic isoperoxidase patterns were quite uniform among the bush and vine watermelon lines. Although the growth responses of the GA-treated bush watermelon lines were different, their peroxidase patterns were identical. Hence, the watermelon isoperoxidases· do not appear to be associated with dwarfing mechanisms. The vine muskmelon lines exhibited much darker anodic bands than did the bush lines, and two of the cathodic isoperoxidases present in the vine muskmelon lines were absent from the bush lines. Gibberellin treatment stimulated growth in both the bush and vine muskmelon lines, and alleviated some of the isoperoxidase differences between them. Comparisons of isoperoxidase patterns among the Cucurbita species and among Cucurbitaceae genera indicated a potential for such comparisons in assessing phylogenetic relationships among the species and particularly among the genera of Cucurbitaceae.
Covers not scanned.
Keywords: Peroxidase; Cucurbitaceae